Analisis Minat Mahasiswa Program Studi Pendidikan Ekonomi Universitas Palangka Raya Untuk Menjadi Wirausaha - Liling Lenlioni; Sundari, Sundari; Rahman, Rahman; Holga, Holga; Aulia, Monica (Journal Pendidikan Ilmu Pengetahuan Sosial, 2025)
Opportunities to increase students' interest in entrepreneurship are still very open. Entrepreneurship training programs, inspirational seminars, and the provision of business incubator facilities at universities can help build a positive attitude towards entrepreneurship. In the Economics Education Study Program, Faculty of Teacher Training and Education, Palangka Raya University, there are courses such as Entrepreneurship and Small Business Management courses that can be a tool to foster entrepreneurial interest among students, so that through these courses, it can be a driving force for students to become entrepreneurs after completing college. Therefore, the Economics Education Study Program views entrepreneurship not only as an additional skill, but as a core competency that must be possessed by graduates. Students of the economic education study program are expected to understand the principles of economics and be able to apply them in entrepreneurial practices, so that they can become the driving force of economic development in the region and nationally